Study on internal stress damage detection in long-distance oil and gas pipelines via weak magnetic method; ISA Transactions; Vol. 89 - Liu Bing; He Luyao; Ma Zeyu; Zhang Hai; Sfarra S. Stefano; Fernandes H. C. Henrique Coelho; Perilli S. (2019, 2019)
Title screen